An adult case of Bland-White-Garland syndrome with collaterals from giant right coronary artery and bronchial artery - Tobita, Takashige; Arashi, Hiroyuki; Fukushima, Kenji; Hagiwara, Nobuhisa (Journal of cardiology cases, 2017)
Bland-White-Garland syndrome (BWG) is a congenital heart disease characterized by anomalous origin of left coronary artery from main pulmonary artery. The anomaly causes significant myocardial ischemia, mitral insufficiency, and high infant mortality. Several investigators have reported that the subjects who survived to adulthood showed extensive collateral flow from right coronary artery (RCA). We report a case of newly diagnosed BWG in an elderly patient who had well-developed collaterals from aneurysmal giant RCA and bronchial artery, which were identified by coronary angiography with multi-detector computed tomography. <Learning objective: Structural heart disease is occasionally hard to assess with invasive angiography. In this case, multi-detector computed tomography demonstrated complicated structure of anomalous coronary morphology including collateral sources from extra-cardiac anastomoses. The severity of anomaly related myocardial ischemia was evaluated by image fusion with radionuclide myocardial perfusion. Multimodal imaging approach can provide comprehensive and incremental information.>